IHI ID 24 Improving door-to-groin puncture time for acute stroke patients in the ER with large vessel occlusion. (December 2018) - Dharia, Robin; Carney, Megan; O'Connor, Mackenzie; D'Ambrosio, Robin
Abstract : Background: Given the rapid increase in endovascular-eligible acute ischemic stroke patients, it became imperative to improve and streamline our stroke alert algorithm for ER patients particularly given the two city blocks between the ER and endovascular lab. Delays in door-to-groin puncture time (DTG) for stroke patients with large vessel occlusions are associated with worse clinical outcomes. Objectives: To improve DTG time, an interdisciplinary quality committee was formed. This committee identified barriers by retrospective data review, developed novel QI approaches, and implemented a redesigned stroke algorithm incorporating evidence-based practices and a team approach (figures 1 and 2). Methods: A new stroke alert protocol was implemented and data was prospectively collected for six months for two groups of patients: Transfers from ER for possible LVO who underwent thrombectomy, Transfers for possible LVO but deemed not a candidate for thrombectomy. The co–primary outcomes were DTG time and door–to–door (ER–>endovascular lab) time. Retrospective comparison data was obtained from 2015 to 2017. Results: Average DTD times for 2015, 2016, 2017 were 114, 162, 120 min and the average DTG times were 263, 136, and 165 min, respectively. After enactment of the new algorithm, our DTD time decreased to 96 min and most importantly, the DTG time decreased to 104 min (figure 3 ). Conclusions: We report that an emphasis on quality improvement and resulting efficient stroke alert algorithm decreased our DTG time for acute stroke patients with large vessel occlusion undergoing mechanical thrombectomy. By decreasing time to reperfusion, we decrease core infarct size and ultimately improve patients functional outcomes.